Special Administrative Law Within the System of the Defence and Security Regulations in Bosnia and Herzegovina (Kriminalističke teme, 2006)
This article addresses very important issues related to the area of administrative law that are reflected to the general security of the state of Bosnia and Herzegovina. That is, first of all, jurisdiction over security agencies. Author with very strong arguments explains why it is the „must "for the police to be organized on the level of the BiH state. He analyses defense and security as special administrative areas, and draws distinction between unitarianism and majorisation of the state.